Long-term exposure to formaldehyde induced down-regulation of SPO11 in rats. (2nd January 2021) - Ge, Pan; Zhang, Xiang; Yang, Yan-qi; Lv, Mo-qi; Zhou, Dang-xia
Abstract: Objective: Formaldehyde, a ubiquitous environmental contaminant, has long been suspected of causing male reproductive injury, but the underlying molecular mechanism remains largely unknown. SPO11 is a meiosis-related gene, whose absence can cause spermatogenesis arrest. Materials and methods: The present study aimed to explore the role of SPO11 in male reproductive injury induced by long-term formaldehyde exposure, so as to further understand the molecular mechanism of formaldehyde-induced male reproductive toxicity. Adult male Sprague-Dawley rats ( n  = 24, 245 ± 22 g) were randomly divided into four groups of six ( n  = 6) and were exposed to formaldehyde gas at doses of 0 (control), 0.5, 2.46 and 5 mg/m 3, respectively, via inhalation for 8 consecutive weeks. Results and dissussion: The expression levels of SPO11 were detected in testicular tissues by real-time quantitative polymerase chain reaction, immunofluorescence, and Western blot. The results indicated that the expression of SPO11 was inhibited by formaldehyde exposure in a dose-dependent manner. Furthermore, the histopathological results showed that testicular seminiferous tubules were atrophied, spermatogenic cells were decreased and the lumina were oligozoospermic in the 2.46 and 5 mg/m 3 formaldehyde exposure groups. Combined with the morphometric results, we found that the downregulated expression levels of SPO11 were consistent with the changes of testicular seminiferous tubule diameter and seminiferous epithelium height in testicular tissue, suggesting that SPO11 might be one of the main targets of formaldehyde reproductive toxicity. Conclusions: In conclusion, our findings indicated that SPO11 might be related to male reproductive injuries induced by long-term formaldehyde exposure.